Lo social como proceso: la transductividad ontogenética de las prácticas sociales - Ferreira, Miguel A. V. (Nómadas. Critical Journal of Social and Juridical Science, 2009)
Taking social practices as a start point to comprehend social nature raises reflexivity as core concept; but this concept, in our opinion, has been misunderstood by Sociologíal Theory and we try to stablish, then, a critical distance from it. So, we propose an alternative concept: “transductivity”. The theoretical fundation of this concept comes from ontogenetic proposals pointed by Simondon.